Keteladanan Yesus Mengajar Murid-Murid dan Implikasinya bagi Pelayanan Sekolah Minggu - Endah Mulyani; Semuel Ruddy Angkouw; Andreas Joswanto (REAL DIDACHE: Journal of Christian Education, 2022)
Sunday School service is very important in the Church. Therefore, it cannot be ignored but must get a sufficient portion of attention and full support from the church. Sunday School Waiter. It is not easy, it needs knowledge and skills to teach and educate children with the aim of guiding children to know God early. In writing this scientific work, researchers use qualitative methods, namely describing data. While the main source of study is journal articles and books that discuss the example of Jesus in teaching students and its implications in the ministry of Sunday School. Urain in this article shows that Jesus the Great Teacher has given an example in teaching effective and successful disciples. Jesus' teaching was great in teaching him eternal life. His way of teaching is also very clear in the presentation of the material. His example in terms of sacrifice, mercy and honesty greatly adds to the quality of His teachership as a Rabbi. Jesus not only gave teaching, but also discipleship to the end of the world. Childhood is an important stage in the formation of personality basics later in life. Jesus' example in teaching the students is very effective and greatly supports the success of Sunday School ministry.Keywords: The example of Jesus, teaching, Ministry, Sunday SchoolAbstrakPelayanan Sekolah Minggu sangat penting di dalam Gereja. Karena itu, tidak bisa diabaikan begitu saja namun harus mendapatkan porsi perhatian yang cukup dan dukungan penuh dari gereja. Pelayan Sekolah Minggu. tidaklah mudah, perlu pengetahuan dan ketrampilan guna mengajar dan mendidik anak-anak dengan tujuan membimbing anak untuk mengenal Tuhan sejak dini. Dalam penulisan karya ilmiah ini peneliti menggunakan metode kualitatif yaitu menjabarkan data sedangkan sumber utama kajian adalah artikel jurnal dan buku-buku yang membahas tentang keteladanan Yesus dalam mengajar murid-murid dan implikasinya dalam pelayanan Sekolah Minggu. Uraian pada artikel ini menunjukkan Yesus Guru Agung itu telah memberikan keteladanan dalam mengajar para murid yang efektif dan berhasil. Pengajaran Yesus sangat hebat dalam mengajarkan nilah hidup kekal. Cara mengajar-Nya sangat jelas dalam pemaparan materi. Keteladanan-Nya dalam hal pengorbanan, belas kasihan dan kejujuran sangat menambah kualitas keguruan-Nya sebagai seorang Rabi. Yesus bukan hanya memberikan pengajaran saja, tetapi juga pemuridan sampai akhir dunia. Masa anak-anak merupakan tahap penting dalam pembentukan dasar-dasar kepribadian di kemudian hari. Keteladanan Yesus di dalam mengajar para murid sangat efektif dan sangat menunjang keberhasilan pelayanan Sekolah Minggu.Kata kunci: keteladanan Yesus; mengajar; pelayanan; sekolah minggu